Planning for Climate Resilient Barangays in the Philippines: The Case of Barangay Tumana in Marikina City, Metro Manila - Espina, Nicasio B (Consilience, 2018)
The Philippines is among the countries most threatened by climate change. This combined with other human and developmental factors compounds the challenge that barangays, the smallest political and administrative units in the country, face: to build and scale-up local resilience. This paper presents the case of Barangay Tumana in Marikina City, Philippines, the second most populated barangay in the city and the most devastated when Typhoon Ondoy (international name: Ketsana) hit the country in 2009. The study examines key hazards and elements of the communities in Barangay Tumana that contribute to its susceptibility to climate-related impacts, using the definition of the United Nations Framework Convention on Climate Change (UNFCCC) to frame the process of analysis. In particular, it characterizes the biophysical/environmental risks and socioeconomic/demographic vulnerabilities of the communities (exposure and sensitivity elements) in Barangay Tumana that can be addressed through planning in order to further community resilience and enhance long-term quality of life (Ensor, and Berger, 2009). These risks and vulnerabilities are established through various quantitative and qualitative methods of data gathering and analysis, including questionnaire surveys, key informant interviews, Geographic Information System (GIS) analysis, reviews of key local documents and related literature, and a multi-stakeholder validation and consultation. Policy options to build barangay resilience in the context of climate change are then recommended.